2010
DOI: 10.1074/jbc.m110.135731
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplet-associated Proteins Are Involved in the Biosynthesis and Hydrolysis of Triacylglycerol in Mycobacterium bovis Bacillus Calmette-Guérin

Abstract: Mycobacteria store triacylglycerols (TGs) in the form of intracellular lipid droplets (LDs) during hypoxia-induced nonreplicating persistence. These bacteria are phenotypically drug-resistant and therefore are believed to be the cause for prolonged tuberculosis treatment. LDs are also associated with bacilli in tuberculosis patient sputum and hypervirulent strains. Although proteins bound to LDs are well characterized in eukaryotes, the identities and functions of such proteins have not been described in mycob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 51 publications
1
78
0
Order By: Relevance
“…Furthermore, pathogenic Mycobacterium species usurp and hydrolyze TAG from host LDs within foamy macrophages, incorporating the resulting fatty acid products into its own LDs for use as an energy source during NRP (58,69,71). Consistent with this observation, Mycobacterium bovis BCG strains that are inhibited in their ability to mediate TAG hydrolysis are attenuated for survival in vitro during and following resuscitation from NRP (60,61). Similarly, an M. tuberculosis mutant deleted in triacylglycerol-1 synthase (⌬tgs1), an enzyme used to make TAGs, is compromised in its ability to accumulate intracellular TAGs and is unable to enter into NRP in an in vitro human TB granuloma model (73).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, pathogenic Mycobacterium species usurp and hydrolyze TAG from host LDs within foamy macrophages, incorporating the resulting fatty acid products into its own LDs for use as an energy source during NRP (58,69,71). Consistent with this observation, Mycobacterium bovis BCG strains that are inhibited in their ability to mediate TAG hydrolysis are attenuated for survival in vitro during and following resuscitation from NRP (60,61). Similarly, an M. tuberculosis mutant deleted in triacylglycerol-1 synthase (⌬tgs1), an enzyme used to make TAGs, is compromised in its ability to accumulate intracellular TAGs and is unable to enter into NRP in an in vitro human TB granuloma model (73).…”
Section: Discussionsupporting
confidence: 63%
“…LD production is induced in M. tuberculosis under conditions that also promote the establishment of NRP (56). Furthermore, it has been shown that M. tuberculosis mobilizes TAGs contained within LDs as an energy source during NRP (58)(59)(60)(61). To determine whether Rv2744c regulated the survival of M. tuberculosis during NRP, wild-type H37Rv, the ⌬Rv2744c mutant, and the ⌬Rv2744c variant overproducing Rv2744c were assessed using the rapid anaerobic dormancy (RAD) model (39).…”
Section: Fig 2 Rv2744c Forms Higher-order Homo-oligomeric Structures mentioning
confidence: 99%
“…For example, mammalian PLIN 1, 2, and 3 can be targeted to bacterial lipid droplets ( 99 ), and Drosophila Lsd1 and Lsd2 can be targeted to the lipid droplets of CHO cells ( 100 ). Furthermore, Dictyostelium Lsd1 can be targeted to CHO cell lipid droplets ( 100 ), and fi ve mycobacterial proteins can be targeted to yeast lipid droplets ( 43 ). Therefore, it appears that these lipid droplet structural proteins from diverse species have certain properties in common that allow them to be properly targeted to lipid droplets.…”
Section: Putative Structural Proteins Of Lipid Dropletsmentioning
confidence: 99%
“…A family of 24 carboxyl ester hydrolases called "lip" genes (lipC to Z, except K and S) has been predicted to play a role in lipid catabolism (14). Among these, only a few have been functionally characterized and related to mycobacterial dormancy and resuscitation (15)(16)(17)(18).…”
mentioning
confidence: 99%